2021
DOI: 10.3892/mmr.2021.12488
|View full text |Cite
|
Sign up to set email alerts
|

Role of tumor necrosis factor receptor‑associated factor 6 in pyroptosis during acute pancreatitis

Abstract: Acute pancreatitis (AP) is hypothesized to be related to the activation of an inflammatory response induced by pyroptosis. The aim of the present study was to investigate the potential role of tumor necrosis factor receptor-associated factor 6 (TRAF6) in pyroptosis in an AP rat model and the human pancreatic ductal epithelial HPDE6C7 cell line. In vivo, AP was induced by intraperitoneal injection of caerulein (CAE) in rats. The rats were sacrificed at 24 or 48 h after the final CAE injection. In vitro, HPDE6C7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
3
8
0
Order By: Relevance
“…Subsequently, we investigated whether regulating TRAF6 affects HTG-AP via the pyroptosis pathway, which would indicate the involvement of TRAF6 in the pathogenesis of HTG-AP. First, this finding is consistent with a previous study in which TRAF6 was found highly-expressed in both in vitro and in vivo AP and HTG-AP models, especially in HTG-AP groups [ 24 ]. Next, the TRAF6 gene was knocked down by siRNA-transfection in pancreatic acinar cells according to the most significant knockout efficiency in previous study [ 44 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Subsequently, we investigated whether regulating TRAF6 affects HTG-AP via the pyroptosis pathway, which would indicate the involvement of TRAF6 in the pathogenesis of HTG-AP. First, this finding is consistent with a previous study in which TRAF6 was found highly-expressed in both in vitro and in vivo AP and HTG-AP models, especially in HTG-AP groups [ 24 ]. Next, the TRAF6 gene was knocked down by siRNA-transfection in pancreatic acinar cells according to the most significant knockout efficiency in previous study [ 44 ].…”
Section: Discussionsupporting
confidence: 92%
“…Hence, we conducted a series of experiments to determine the function and underlying mechanism of participation of TRAF6 in pyroptosis during AP. In our previous studies, we found high expression of TRAF6 in cerulein-induced AP in vivo, and overexpression of TRAF6 gene was found to activate pyroptosis to induce AP in vitro [ 24 ]. Therefore, we hypothesized that TRAF6 may mediate cerulein-induced HTG-AP by regulating pyroptosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, high concentrations of pancreatitis-inducing factors reverse these effects and impair PACs and PDECs ( 13 - 16 ). In our previous studies, AP was mimicked in PDECs in vitro using CAE and led to pyroptosis and barrier function impairment, in line with the results in a rat model of AP ( 17 - 19 ). However, the role of autophagy in this in vitro model has not been determined.…”
Section: Introductionsupporting
confidence: 79%
“…Previous studies have reported that barrier disfunction in PDECs is a major contributor to the occurrence of pancreatitis ( 6-9 ). Our previous study revealed that the synthetic cholecystokinin analogue caerulein (CAE) induced AP in the human pancreatic ductal epithelial cell line HPDE6-C7( 10 ). In addition, high-fat diet-derived FFAs can impair intestinal epithelial cell permeability ( 11-13 ); nonetheless, the effect of HTG on PDECs in AP is incompletely understood.…”
Section: Introductionmentioning
confidence: 99%